DAMPAK PENGGUNAAN TEKNOLOGI ARTIFICIAL INTELLIGENCE PADA KEGIATAN PEMBELAJARAN MAHASISWA - Jannatul Ma'wa, Puteri (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM Azramedia Indonesia, 2024)
This research aims to analyze the impact of using artificial intelligence (AI) on students in learning activities. The research was conducted using literature review method to collect data from various relevant literatures. The results show that the use of AI in education can have a positive impact in the form of time efficiency, wider access to information, and better personalization of learning. AI also improves time efficiency, allows students to allocate more time for more value-added activities, and provides convenience in asking questions and finding answers at any time. However, on the other hand, over-reliance on AI can reduce students' critical and independent thinking skills. AI also has the potential to reduce creativity and innovation because students tend to follow the solutions provided by AI without thinking deeper. However, there are also negative impacts, such as dependence on technology, decreased creativity, and decreased student literacy skills. It is important for students to use AI wisely so as not to hinder the development of their critical and innovative thinking skills.